Low Vitamin D Status Has an Adverse Influence on Bone Mass, Bone Turnover, and Muscle Strength in Chinese Adolescent Girls 1,2 - Leng, Huat Foo; Qian, Zhang; Kun, Zhu; Guansheng, Ma; Xiaoqi, Hu; Greenfield, Heather; Fraser, David R. (American Society for Nutrition, 2009)
Our goal in this cross-sectional study was to investigate the influence of low-vitamin D status on bone mass, bone turnover, and muscle strength in 301 healthy Chinese adolescent girls. Blood plasma 25-hydroxyvitamin D [25(OH)D] was measured by RIA and plasma and urine biomarkers of bone turnover were measured. Bone mineral content (BMC) and density and bone area for the whole body and the distal and proximal forearm were measured by dual energy X-ray absorptiometry. When vitamin D deficiency was defined as a serum 25(OH)D concentration of #50 nmol/L and severe deficiency as ,25 nmol/L, 57.8% of subjects were vitamin D deficient and 31.2% were severely deficient. Multivariate analysis shows that girls with adequate vitamin D status had higher size-adjusted BMC for the whole body (P , 0.001), distal forearm (P,0.001), and proximal forearm (P,0.01) than those with poorer vitamin D status after adjusting for body size, handgrip strength, physical activity, and dietary intakes of calcium and vitamin D. Similar results were also found for handgrip muscle strength. Participants with adequate vitamin D status had significantly lower concentrations of bone alkaline phosphatase in plasma and deoxypyridinoline:creatinine ratio in urine compared with those of the vitamin D-deficient girls. Adolescent girls with adequate vitamin D status had significantly higher bone mass and muscle strength compared with those with poor vitamin D status. This may be attributed in part to a lower rate of bone remodeling with adequate vitamin D status. These findings suggest that adequate vitamin D status during adolescence is important for optimizing bone mass, which may lead to higher peak bone mass at maturity. Poor vitamin D status also compromises forearm muscle strength.